(untitled) (Journal of the College of Basic Education, 2025)
With the rapid development of technology and the digital transformation that the world is witnessing, the family is facing new and increasing challenges in terms of raising and educating children in the digital age, and here lies the problem of the research, as technology has become an integral part of people’s lives, as children and adolescents use smart devices and the Internet on a daily basis for studying, communicating, entertainment, and even forming a self-identity. With this change, new challenges emerge for the family in terms of its ability to balance between benefiting from technology and maintaining the correct educational guidance. From the above, the current research aims to identify the most prominent educational challenges facing the family in the digital age, and to achieve this goal, the researcher used the descriptive inductive approach. The study reached a set of challenges related to the (social, religious, moral, cultural) aspect. In light of these challenges, the researcher developed a set of recommendations.